Denetçilerin denetim kalitesine ilişkin teorik algılarının demografik değişkenlere göre incelenmesi - Rustamlı, Teymur (My University, 2024)
Bu çalışmada, denetçilerin (iç denetçi, dış denetçi/ kanuni denetçi, bağımsız denetçi) görüşlerine göre, denetim kalitesine ilişkin teorik algılarının incelenmesi amaçlanmıştır. Araştırmada tarama modeli kullanılacaktır. Araştırma sonucuna göre; katılımcıların denetim kalitesi algıları ölçek ve alt boyutları ortalamanın üstünde çıkmıştır. Cinsiyete göre incelemede; kadın ve erkeğe göre değişmediği yani farklılık çıkmamıştır. Medeni duruma göre incelemede; evli ve bekara göre değişmediği yani farklılık çıkmamıştır. Süreç alt boyutu yaş değişkenine göre farklılık çıkmıştır. Bu durumda süreç alt boyutunda; 51-60 yaş grubun süreç algısı 61 yaş ve üstü gruplarından daha yüksek çıkmıştır. Diğer yandan geriye kalan alt boyut ve ölçek geneli yaş gruplarına göre farklılık göstermemektedir. Süreç alt boyutu ve denetim kalitesi algıları genel ölçeğinde mesleki deneyim yılı değişkenine göre farklılık çıkmıştır. Buna göre süreç alt boyutunda; 31 yıl üstü mesleki deneyim sahibi grubun süreç algısı 11 - 20 yıl ve 21 - 30 yıl grubundan daha yüksek çıkmıştır. Katılımcıların Denetim kalitesi algıları ölçeği genel boyutunda 1 - 10 yıl grubun Denetim kalitesi genel algısı 11 - 20 yıl ve 21 - 30 yıl grubundan daha yüksek çıkmıştır. Diğer yandan geriye kalan alt boyut ve ölçek geneli mesleki deneyim yılına göre farklılık göstermemektedir. Süreç ve çıktı alt boyutu ile denetim kalitesi algıları ölçeği unvan değişkenine göre farklılık çıkmıştır. Araştırma kapsamındaki katılımcıların, girdi alt boyutuyla süreç alt boyutu arasında anlamlı ve pozitif bir ilişki vardır. Yine katılımcıların, süreç alt boyutuyla çıktı süreç alt boyutu arasında anlamlı ve pozitif bir ilişki vardır.

This study aims to examine the theoretical perceptions of auditors (internal auditor, external auditor/ statutory auditor, independent auditor) regarding audit quality according to their opinions. The screening model will be used in the research. According to the research results; the participants' audit quality perceptions were above average in the scale and sub-dimensions. In the examination according to gender; it did not change according to women and men, i.e. there was no difference. In the examination according to marital status; it did not change according to married and single, i.e. there was no difference. In the process sub-dimension, there was a difference according to the age variable. In this case, in the process sub-dimension; the process perception of the group between the ages of 51-60 was higher than the groups of 61 and above. On the other hand, the remaining sub-dimension and the scale in general did not differ according to age groups. In the process sub-dimension and the audit quality perceptions in general scale, there was a difference according to the variable of years of professional experience. Accordingly, in the process sub-dimension; the process perception of the group with 31 years and above professional experience was higher than the groups of 11-20 years and 21-30 years. In the general dimension of the Audit quality perception scale of the participants, the general perception of the Audit quality of the 1-10 year group was higher than the 11-20 and 21-30 year groups. On the other hand, the remaining sub-dimensions and the scale in general did not differ according to the years of professional experience. The process and output sub-dimensions and the audit quality perception scale differed according to the title variable. There is a significant and positive relationship between the input sub-dimension and the process sub-dimension of the participants within the scope of the research. Again, there is a significant and positive relationship between the process sub-dimension and the output process sub-dimension of the participants.
Examination of theoretical perceptions of auditors on audit quality according to demographic variables
Keywords: Accounting; audit quality; Auditing; auditor; denetçi; Denetim; denetim kalitesi; Muhasebe; teorik algı Audit; theoretical perception